Pengaruh Stres Kerja dan Beban Kerja terhadap Kepuasan Kerja Pegawai pada Kantor Badan Pendapatan Daerah Kabupaten Empat Lawang - Emila Sholiha; M. Pahlan; Darwin Kesuma; Heri Fitriadi (Journal on Education, 2025)
This study aims to analyze the influence of work stress and workload on employee job satisfaction at the Regional Revenue Agency Office of Empat Lawang Regency. This research employs a quantitative method with a survey approach, where data was collected through questionnaires distributed to 47 employees. The data analysis technique used is multiple linear regression analysis to determine the influence of the two independent variables on the dependent variable. The results of the study indicate that work stress has a significant negative impact on employee job satisfaction, meaning that the higher the level of work stress experienced by employees, the lower their job satisfaction. On the other hand, workload has a significant positive impact on job satisfaction, indicating that a well- managed workload can enhance employee job satisfaction. These findings have important implications for management in developing strategies to manage employee stress and workload to enhance job satisfaction and organizational productivity.